Seroprevalence of infection-induced SARS-CoV-2 antibodies among health care users of Northern Italy: results from two serosurveys (October-November 2019 and September-October 2021). (November 2022) - Vicentini, Costanza; Bordino, Valerio; Cornio, Alessandro Roberto; Meddis, Davide; Marengo, Noemi; Ditommaso, Savina; Giacomuzzi, Monica; Memoli, Gabriele; Furfaro, Gabriella; Mengozzi, Giulio; Ricucci, Valentina; Icardi, Giancarlo; et al.
Highlights: SARS-CoV-2 seroprevalence in Italy among samples from autumn 2019 was investigated. A second serosurvey was conducted in September-October 2021. Two seropositive individuals were identified in 2019 (before the first official case in Italy). Independent testing confirmed results. Estimated seroprevalence was 0.27% and 6.21% in 2019 and 2021, respectively. Abstract: Objectives: The objective was to estimate the seroprevalence of SARS-CoV-2 in autumn 2019 (before case zero was identified in Italy) and 2021 among residual sera samples from health care users in the Piedmont region of northwestern Italy. Methods: Two serosurveys were conducted. Using a semiquantitative method, samples were tested for the presence of immunoglobulin G (IgG) antibodies against the S1 domain of the spike protein. Samples with positive test results from the 2019 survey were independently retested using a multiplex panel to detect IgG antibodies against the receptor binding domain, S1 and S2 domains, and nucleocapsid. Samples with positive test results from the 2021 survey underwent repeat testing with enzyme-linked immunosorbent assay to detect anti-nucleocapsid IgG antibodies. Prevalence rates according to gender and age groups, together with their respective 95% confidence intervals (CIs), were calculated. Results: Overall, the proportion of samples with positive test results was 2/353 in 2019 and 22/363 in 2021, with an estimated seroprevalence of 0.27% (95% CI 0-1.86) and 6.21% (95% CI 3.9-9.31) in 2019 and 2021 respectively. Conclusion: Results of this study support the hypothesis that the virus was circulating in Italy as early as autumn 2019. The role of these early cases in broader transmission dynamics remains to be determined.